2017
DOI: 10.1371/journal.pone.0181329
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics of the anchovy genus Encrasicholina in the Northwest Pacific

Abstract: The anchovy genus Encrasicholina is an important coastal marine resource of the tropical Indo-West Pacific (IWP) region for which insufficient comparative data are available to evaluate the effects of current exploitation levels on the sustainability of its species and populations. Encrasicholina currently comprises nine valid species that are morphologically very similar. Only three, Encrasicholina punctifer, E. heteroloba, and E. pseudoheteroloba, occur in the Northwest Pacific subregion of the northeastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
1
7
1
Order By: Relevance
“…Divergence times. Our separate mtDNA-and nDNA--based estimates of divergence times suggest that conflicting results reported by previous mtDNA (Lavoué et al, 2013(Lavoué et al, , 2017b and mtDNA+nDNA (Bloom, Lovejoy, 2014) studies on clupeiform divergence times are partially due to the different genes in these datasets. We estimated divergence times for major clupeiform clades that were nearly always youn- Fig.…”
Section: Concordant and Conflicting Phylogenetic Relationshipscontrasting
confidence: 67%
See 2 more Smart Citations
“…Divergence times. Our separate mtDNA-and nDNA--based estimates of divergence times suggest that conflicting results reported by previous mtDNA (Lavoué et al, 2013(Lavoué et al, , 2017b and mtDNA+nDNA (Bloom, Lovejoy, 2014) studies on clupeiform divergence times are partially due to the different genes in these datasets. We estimated divergence times for major clupeiform clades that were nearly always youn- Fig.…”
Section: Concordant and Conflicting Phylogenetic Relationshipscontrasting
confidence: 67%
“…Age estimates for the MRCA of Pristigasteridae and Clupeidae were particularly different between the mtDNA and nDNA datasets. Differences between in our age estimates from previous studies are likely also due to the exclusion of fossils used in previous studies because of uncertainty regarding their placement (Lavoué et al, 2017b): †Gasteroclupea branisai, previously used to set a minimum age for the MRCA of Pristigasteridae, †Nolfia riachuelensis, previously used to set a minimum age for the MRCA of Clupeidae (Bloom, Lovejoy, 2014), and †Lecceclupea ehiravaensis to set a minimum age for the MRCA of the clupeid lineage Ehiravini (Gilchristella + Clupeichthys; Lavoué et al, 2013).…”
Section: Concordant and Conflicting Phylogenetic Relationshipsmentioning
confidence: 90%
See 1 more Smart Citation
“…The authors stressed the probable role of bacterial leakage or translocation through the sutures to justify these results, supported by the well-known appearance of most adhesions in the area of bowel anastomosis [80] . Moreover, recent studies have consistently demonstrated that serotonin production is lower in GF mice and that it is probably mediated by SCFA production [81 , 82] .…”
Section: Methodsmentioning
confidence: 99%
“…The 13 samples collected from Chongming, Luchao, and Jingjiang were considered as the anadromous population (SH, n = 13), whereas the other samples were treated as the resident populations. Five samples of C. mystus collected from the Yangtze River were used as outgroups, since it was found closely related to Coilia nasus species complex (Lavoué et al, ). Most samples of the resident populations were collected after October, when the migratory fish had already left freshwater habitat.…”
Section: Methodsmentioning
confidence: 99%